The use of fluorescent protein-tagged carbohydrate-binding modules to evaluate the influence of drying on cellulose accessibility and enzymatic hydrolysis. Issue 45 (21st July 2020) - Mboowa, Drake; Khatri, Vinay; Saddler, Jack N.
Abstract : Drying restricts cellulose accessibility at macro- and micro-scale of fiber structure with restriction at macro-fiber significantly limiting accessibility to micro-fibrils. Abstract : The influence of drying on cellulose accessibility and enzymatic hydrolysis was assessed. Dissolving pulp was differentially dried by freeze-, air- and oven-drying at 50 °C and subsequently hydrolyzed using the commercial CTec 3 cellulase preparation. It was apparent that drying reduced the ease of enzymatic hydrolysis of all of the substrates with a pronounced reduction (48%) exhibited by the oven-dried pulp. To assess if the ease of hydrolysis was due to enzyme accessibility to the substrate, microscopy (SEM), FTIR spectroscopy, water retention value (WRV), fiber aspect ratio analysis, Simons' stain and the selective binding of Fluorescent Protein-tagged Carbohydrate Binding Modules (FP-CBMs): CBM3a (crystalline cellulose) and CBM17 (amorphous cellulose) in combination with confocal laser scanning microscopy (CLSM) were used. The combined methods indicated that, if the gross characteristics of the substrate limited enzyme accessibility, the cellulases, as represented by the FP-CBMs, could not in turn access the finer structural components of the cellulosic substrates.